Constructing Legitimacy in "Stone" and "Words" during Cuba's Second Republic: Building and Contesting Fulgencio Batista's José Martí. - GUEVARA, DANIEL J. FERNÁNDEZ (History & Memory)
The centennial of José Martí's birth and the construction of monuments and buildings dedicated to his memory in Havana's Civic Plaza in 1953 continued a long-standing tradition of utilizing the martyr's memory to fit the priorities of the Cuban state. This article focuses on how this and other celebrations in commemoration of Cuba's War of Independence heroes that were held during the illegitimate regime of Cuban dictator Fulgencio Batista (1952-58) reflected the dictator's claim that his 1952 coup was a unique and authentic "revolution" but also became contested spaces where Cuba's social and political actors asserted their rights as faithful interpreters of Cuba's independence struggles and heirs of its heroes.